A Post-COVID-19 Economic Recovery Model: The national domestic economic auto-sustainability Model (NDEAS-Model) - Estrada, Mario Arturo Ruiz (AEI Insights, 2021)
The significant damage of COVID-19 on the world economy forces us to reconsider a deep restructuration domestically and internationally in the next few years. This paper suggests a Post-COVID-19 reconstruction model is called “The National Domestic Economic AutoSustainability Model (NDEAS-Model).” The NDEAS-Model proposes four economic platforms: (i) the domestic education and technical training standardization platform (P1); (ii) the domestic productive infrastructure and transportation platform (P2); (iii) the selective strategic trade, investment, and tourism protection platform (P3); (iv) the environmental and natural resources management platform (P4). The main objective of NDEAS-Model is to avoid imported massive pandemic diseases, non-sustainable and weak food security platforms, and job diversion, respectively.